UMPSA Takes Third Place in the 2023 Pahang Chief Minister's Parliamentary Malay Debate Cup - Amy Zulaikha, Mohd Ali (UMPSA, 2023)
KUANTAN, 7 September 2023 - The 2023 Pahang Chief Minister's Parliamentary Malay Debate Cup reached its pinnacle with the announcement of winners held at the Grand Darul Makmur Hotel in Kuantan recently.